2008
DOI: 10.1108/02652320810894406
|View full text |Cite
|
Sign up to set email alerts
|

What determines Turkish customers' acceptance of internet banking?

Abstract: PurposeThe purpose of this article is to provide an insight into the determinants of customers' internet banking (IB) acceptance. Therefore, it attempts to address a research need for extending the technology acceptance model (TAM) by adding contextual factors for IB case.Design/methodology/approachA research model reflecting the effects of perceived risk (PR), perceived playfulness (PPL) and perceived behavioral control (PBC) on TAM constructs is proposed. The partial least squares (PLS) procedure is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 78 publications
11
117
0
4
Order By: Relevance
“…Its p-value is < 0.05, posited that H4 is supported. This finding is consistent with previous studies (Celik, 2008;Lin, 2007;Shih and Fang, 2006).…”
Section: Data Analysis and Findingssupporting
confidence: 83%
“…Its p-value is < 0.05, posited that H4 is supported. This finding is consistent with previous studies (Celik, 2008;Lin, 2007;Shih and Fang, 2006).…”
Section: Data Analysis and Findingssupporting
confidence: 83%
“…Which is smellier to the findings of Celik (2008) who study the same factors and finally stated that (PU) and (PEOU) are direct determinants of customers' attitudes towards using internet banking.…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Celik (2008) found that the individuals will have a positive view about new technology that they believe is easy to learn and use. In particular, there are strong indications that the ease of use of e-banking services increases the adoption of these services by customers.…”
Section: Ease Of Usementioning
confidence: 99%